Polysemi i ordböcker - Nikula, Henrik (Nordiske Studier i Leksikografi, 2010)
It is argued that by using a combination of structural-functional grammar and prototype theory polysemy in dictionary entries may be strongly reduced. Within this theoretical framework the kernel meaning is defined by a “digital” semantic component restricting and perspectivating the prototypically structured “analogical” component. The analogical component is context-sensitive thus allowing less prototypical referents to be related to the digital component without causing any kind of restructuring of the kernel meaning; in this sense there is no process of coercion needed. – The above theory is tested on some entries in the Swedish dictionary Svensk ordbok (2009).